2019
DOI: 10.1177/1758835919846375
|View full text |Cite
|
Sign up to set email alerts
|

Cotargeting Plk1 and androgen receptor enhances the therapeutic sensitivity of paclitaxel-resistant prostate cancer

Abstract: Backgrounds: Despite the clinical success of taxanes, they still have limitations, such as chemoresistance. To overcome the limitations of paclitaxel, genetic alterations and targeting effects of altered genes were observed in paclitaxel-resistant cancer. Because paclitaxel-resistant cancer shows high levels of Plk1, a promising target in chemotherapy, the effectiveness of Plk1 inhibitors in paclitaxel-resistant cancer cells has been investigated. Methods: Paclitaxel-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…The role of PLK1 in prostate cancer is not clear at present [ 23 ]. However, numerous studies indicate that PLK1 can act as an oncogene, and PLK-1 inhibitors can effectively inhibit prostate cancer progression [ 24 26 ]. PLK1 can also inactivate other tumor suppressors [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of PLK1 in prostate cancer is not clear at present [ 23 ]. However, numerous studies indicate that PLK1 can act as an oncogene, and PLK-1 inhibitors can effectively inhibit prostate cancer progression [ 24 26 ]. PLK1 can also inactivate other tumor suppressors [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polo-like kinase 1 (Plk1) has been shown to be involved in chemoresistance, so Plk1-targeted therapies could possibly reduce or eliminate the chemoresistance of cancer cells against anticancer drugs. Genistein was proposed as a Plk1 inhibitor, which effectively downregulates the expression of multidrug resistance protein 1 and multidrug resistance-associated protein 1, key factors inducing chemoresistance in paclitaxel-resistant cancer cells (Shin et al, 2019). The discovery of genistein being a Plk1 inhibitor adds a new horizon for the possible application of genistein as adjuvant in chemotherapy because of its ability to prevent cancer cells from acquiring resistance against the anticancer drugs or due to resensitize drug-resistant cancer cells.…”
Section: Current Limitation and Challengesmentioning
confidence: 99%
“…Previous studies have revealed that PLK1 is highly expressed in several malignancies, and that PLK1 is involved in chemoresistance [ 30 , 31 ]. Moreover, PLK1 is highly expressed in paclitaxel-resistant prostate and lung cancer [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that PLK1 is highly expressed in several malignancies, and that PLK1 is involved in chemoresistance [ 30 , 31 ]. Moreover, PLK1 is highly expressed in paclitaxel-resistant prostate and lung cancer [ 30 ]. To investigate the possibility of improving the efficacy of current treatment regimens for paclitaxel-resistant lung cancer, a paclitaxel-resistant lung cancer cell line was co-treated with the PLK1 inhibitor volasertib combined with the USP7 inhibitor P22077 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation